Climate variability, perceptions of pastoralists and their adaptation strategies: Implications for livestock system and diseases in Borana zone - Ayal, Desalegn Y.; Radeny, Maren A.O.; Desta, Solomon; Gebru, Getachew (Emerald Publishing Limited, 2018)
Purpose: Climate variability and extremes adversely affect the livestock sector directly and indirectly by aggravating the prevalence of livestock diseases, distorting production system and the sector profitability. This paper aims to examine climate variability and its impact on livestock system and livestock disease among pastoralists in Borana, Southern Ethiopia. Design/methodology/approach: Data were collected through a combination of quantitative and qualitative methods using household questionnaire, field observations, focus group discussions and key informant interviews. Areal grid dikadal rainfall and temperatures data from 1985 to 2014 were collected from national meteorological agency. The quantitative and qualitative data were analyzed and interpreted using appropriate analytical tools and procedures. Findings: The result revealed that the study area is hard hit by moisture stress, due to the late onset of rainy seasons, decrease in the number of rainy days and volume of rainfall. The rainfall distribution behavior coupled with the parallel increase in minimum and maximum temperature exacerbated the impact on livestock system and livestock health. Majority of the pastoralists are found to have rightly perceived the very occurrence and manifestations of climate variability and its consequences. Pastoralists are hardly coping with the challenges of climate variability, mainly due to cultural prejudice, poor service delivery and the socio-economic and demographic challenges. Research limitations/implications: Pastoralists are vulnerable to the adverse impact of climate variability and extreme events. Practical implications: The finding of the study provides baseline information for practitioners, researchers and policymakers. Originality/value: This paper provided detailed insights about the rainfall and temperature trend and variability for the past three decades. The finding pointed that pastoralists’ livelihood is under climate variability stress, and it has implications to food insecurity.